1983
DOI: 10.3354/meps011189
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of seasonal natural mortality rates in a copepod population using life-history theory

Abstract: We use inverse optimization techniques and data from Landry (1978) to predict natural mortality rates in a population of the marine, planktonic copepod Acartia clausii. Predicted mortality rates are those that make the observed seasonal pattern of life-history characteristics evolutionarily stable. Our predictions closely approximate the rates observed by Landry. The results imply (1) that the inverse relationship between adult body size and temperature in A. clausii (also widely observed in other copepods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Moreover, some previous studies have noted an apparent association between mortality and temperature among the Copepoda. Myers & Runge (1983, 1986, and showed that the inverse relationship between temperature and adult body size among the marine Copepoda is the opposite of that predicted by life-history theory unless mortality increases with temperature. More recently, Hirst & Kiørboe (2002) used the balanced mortality hypothesis to estimate average mortality rates for a wide range of marine copepod species and found a significant positive association between temperature and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, some previous studies have noted an apparent association between mortality and temperature among the Copepoda. Myers & Runge (1983, 1986, and showed that the inverse relationship between temperature and adult body size among the marine Copepoda is the opposite of that predicted by life-history theory unless mortality increases with temperature. More recently, Hirst & Kiørboe (2002) used the balanced mortality hypothesis to estimate average mortality rates for a wide range of marine copepod species and found a significant positive association between temperature and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…In general, mortality rates are considered to be important in studies related to secondary production, but few estimates of mortality in natural populations of calanoid copepods have been published (see however Matthews et al 1978, Aksnes & Magnesen 1983, Myers & Runge 1983. Landry (1983) suggested that the error in estimation of stage-specific mortality rates will be proportionate to the error in estimating the differences in duration between adjacent instars, and thereby influenced by the isochronal assumption.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of 3.4 % d-' used for the recruiting generation of Calanus glacialis is low compared to estimates of 20 to 30 % d-' given for calanoid copepods from temperate waters (Matthews et al 1978, Aksnes & Magnesen 1983, Myers & Runge 1983. A 2 yr life span for C, glacialis, with an estimated fecundity of 600 eggs female-' and the observed population densities of the varlous life stages, scales the mortality to the correct order of magnitude in the standard run.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of mortality rates of a natural population is important for understanding ecological processes, but mortality is often difficult or impossible to measure (Myers & Runge 1983). The mortality rate of 3.4 % d-' used for the recruiting generation of Calanus glacialis is low compared to estimates of 20 to 30 % d-' given for calanoid copepods from temperate waters (Matthews et al 1978, Aksnes & Magnesen 1983, Myers & Runge 1983.…”
Section: Discussionmentioning
confidence: 99%